Optimalisasi Pendistribusian Dana Zakat, Infaq, Shadaqah Pada Program Ekonomi SUMUT Makmur Dalam Mengentaskan Kemiskinan - Muhammad Ridho (Jurnal Ekonomi dan Keuangan Syariah, 2022)
This research is based on the assumption that the distribution of zakat funds productively through the SUMUT Makmur program can improve the living standards of mutahik to become prosperous. This study aims to determine the optimization of the distribution of productive zakat funds carried out by North Sumatra BAZNAS in the SUMUT Makmur program. This research method uses a qualitative research approach with the type of case study research. Data collection techniques used in this study were observation, interviews and documentation. Based on the results of research and data analysis, it is concluded that the distribution of zakat through the economic program of SUMUT Makmur has been going well by providing economic empowerment assistance. However, significantly the optimization of zakat in the welfare of mustahik has not been optimally well, because BAZNAS SUMUT provides very small business capital assistance and the form of supervision carried out by BAZNAS SUMUT is less than optimal due to the lack of human resources owned so that recipients of venture capital assistance only get results that mediocre.